Composting and Anaerobic Digestion of Food Waste and Sewage Sludge for Campus Sustainability: A Review. (22nd June 2022) - Yaser, Abu Zahrim; Lamaming, Junidah; Suali, Emma; Rajin, Mariani; Saalah, Sariah; Kamin, Zykamilia; Safie, Nurliyana Nasuha; Aji, Nur Aqeela Syuhadah; Wid, Newati
Abstract : Composting and anaerobic digestion have emerged as better options for managing food waste and sewage sludge at the campus level. This review highlights the characteristics of food waste and sewage sludge from various global higher education institutions. The composting and anaerobic digestion processes of food waste and sewage sludge will be reviewed and evaluated. Also, the adoption of composting and anaerobic digestion at various campus levels has been reviewed. The challenges and future direction, focusing on managing university campus composting and anaerobic digestion, are discussed as well. This review paper will significantly contribute to the understanding of the potential for managing and handling campus waste in a natural-friendly manner.